Evaluation of adapted parent training for challenging behaviour in pre-school children with moderate to severe intellectual developmental disabilities: A randomised controlled trial - Royston, Rachel; Absoud, Michael; Ambler, Gareth; Barnes, Jacqueline; Hunter, Rachael; Kyriakopoulos, Marinos; Ondruskova, Tamara; Oulton, Kate; Paliokosta, Eleni; Panca, Monica; Sharma, Aditya; Slonim, Vicky; et al. (PloS one, 2024)
There is limited evidence on the effectiveness of parenting interventions to improve disruptive behaviour in children with intellectual developmental disabilities. This clinical trial evaluated whether an adapted group parenting intervention for preschool children with intellectual developmental disabilities who display challenging behaviour is superior to treatment as usual in England. 261 children aged 30-59 months with moderate to severe intellectual developmental disabilities and challenging behaviour were randomised to either the intervention (Stepping Stones Triple P) and treatment as usual or treatment as usual alone. The primary outcome was the parent-rated Child Behaviour Checklist at 52 weeks after randomisation. A health economic evaluation was also completed. We found no significant difference between arms on the primary outcome (mean difference -4.23; 95% CI: -9.99 to 1.53; p = 0.147). However, a subgroup analysis suggests the intervention was effective for participants randomised before the COVID-19 pandemic (mean difference -7.12; 95% CI: -13.44 to -0.81; p = 0.046). Furthermore, a complier average causal effects analysis (mean difference -11.53; 95% CI: -26.97 to 3.91; p = 0.143) suggests the intervention requires participants to receive a sufficient intervention dose. The intervention generated statistically significant cost savings (-£1,057.88; 95% CI -£3,218.6 to -£46.67) but the mean point estimate in Quality Adjusted Life Years was similar in both groups. This study did not find an effect of the intervention on reducing challenging behaviour, but this may have been influenced by problems with engagement. The intervention could be considered by services as an early intervention if families are supported to attend, especially given its low cost.